Microstructure and Mechanical Properties of As-cast and Heat-treated 935AgCuBeSn Alloys - Siriwan Sakultanchareonchai (Science Faculty of Chiang Mai University, 2019)
Microstructure and mechanical properties of as-cast and heat-treated 935AgCuBeSn alloys were studied. The alloys were cast by lost-wax process in a vacuum inductive furnace. Their chemical composition was determined by inductively-coupled plasma-optical emission spectroscopy. Conventional heat treatment processes of standard Sterling silver alloys were applied viz. holding time in ceramic flash before quenching for 15 min, homogenization at 750 °C for 60 min followed by water quenching, and aging at 350 °C for 15 to 60 min followed by water quenching. Microstructural characterization was carried out by scanning electron microscopy and transmission electron microscopy to study the overall microstructure and precipitates formed by age hardening. It was found that homogenization treatment resulted in partial dissolution and spheroidization of eutectic phases, including a-Ag, b-Cu and a Cu-rich phase containing Ag and Sn, without significant grain coarsening. Aging treatment led to precipitation of fine fcc (Cu,Sn)-rich precipitates. This precipitation led to an improvement in hardness, yield strength and the modulus of resilience of the age-hardened 935AgCuBeSn alloys as compared to those of the conventional 935AgCu alloy.